PEJA: projeto de educação de jovens e adultos ações no campus de Bauru - Zanata, Eliana Marques [UNESP]; Marques, Antonio Francisco [UNESP]; Peres, Érica Coutinho [UNESP]; Souza, Wallace Gabriel [UNESP]; Vieira, Geovane Augusto Gaia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Youth and Adult Education Program - PEJA - UNESP, serves people of UNESP community and neighborhoods. The objectives: rebuilding the personal, social identity and citizenship, providing education of elementary school; enable campus undergraduates experience to organize and develop youth and adult literacy projects; joint training activities, research and discussion of public policy in conjunction with the Group for Study and Research on Popular Education. The following methodology has been adopted: partnerships with institutions located in the periphery; demand survey; use of community spaces for classes. PEJA currently operates in two spaces with grantees and volunteers, one class is installed in a spiritual center, the other space is a truck's own UNESP adapted to be used as a computer room for digital inclusion. The results show that the students of the communities are continuing studies opportunity in elementary school, and has gradually formed their social identity with options for social integration. To graduate students led socio-cultural context of discussions, processes of inclusion and social exclusion and the role of the teacher in society.

O Programa de Educação de Jovens e Adultos – PEJA, atende pessoas da comunidade unespiana e demais bairros da cidade. São objetivos: reconstruir a identidade pessoal, social e cidadania, propiciando escolaridade do ensino fundamental; possibilitar aos alunos de graduação do campus experiência de organizar e desenvolver projetos de alfabetização de jovens e adultos; articulação de atividades capacitação, pesquisa e discussão de políticas públicas em conjunto com o Grupo de Estudos e Pesquisa em Educação Popular. A metodologia comporta: parcerias com instituições localizadas na periferia; levantamento de demanda; uso de espaços comunitários para as aulas. Atualmente o PEJA atua em dois espaços com bolsistas e voluntários, com uma sala está instalada em uma Instituição, o outro espaço é uma carreta da própria UNESP, adaptada para funcionar como sala de informática para inclusão digital. Os resultados apontam que os educandos das comunidades atendidas têm oportunidade de prosseguimento de estudos e gradativamente tem constituído sua identidade social com possibilidade de inserção social. Aos alunos de graduação propiciou discussões de âmbito sócio-cultural, processos de inclusão e exclusão social e o papel do educador na sociedade.
Keywords: Youth and adult education; Literacy; Digital inclusion; Educação de jovens e adultos; Alfabetização; Inclusão digital